2005
DOI: 10.1080/00016470510030698
|View full text |Cite
|
Sign up to set email alerts
|

The economic cost of low back pain in sweden in 2001

Abstract: The cost of illness due to low back pain was substantial, but does not appear to have risen during the last 10-15 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
71
0
11

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(85 citation statements)
references
References 21 publications
3
71
0
11
Order By: Relevance
“…The cost of chronic low back pain has been found to be high in all studies conducted in developed countries (10,11,(19)(20)(21)(22)(23)(24). However, there are no data on developing countries, such as Turkey, in the literature.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The cost of chronic low back pain has been found to be high in all studies conducted in developed countries (10,11,(19)(20)(21)(22)(23)(24). However, there are no data on developing countries, such as Turkey, in the literature.…”
Section: Discussionmentioning
confidence: 93%
“…As a result of the questionnaire survey and phone interviews with 1253 patients with chronic low back pain, the total annual direct cost was found to be 2.6 (22), the total direct cost was found to be 8386±17507 dollars. In a study conducted in Sweden (21), patients that applied to outpatient clinics with complaints of chronic low back pain were given questionnaire forms and they were asked about their inability to go to work in the last 3 months and about their medical expenses in the last 6 months. Annual direct costs and indirect cost were calculated by multiplying by 4 and 2, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…7,12,22,27 It is estimated a point prevalence of back pain around 30% and a lifetime prevalence of 70% to 80%. 1 Although back pain is a highly prevalent condition, in about 85% of cases an accurate pathological diagnosis cannot be made and they are considered either idiopathic or of nonspecifi c origin.…”
Section: Introductionmentioning
confidence: 99%
“…25 Although the direct costs associated with back pain management are increasing, most studies have showed that they are largely related to temporary and permanent work-related disability. 7,8,22,27 The most severe outcome of this condition is permanent disability pension, which is hardly reverted. 20,21 According to two studies carried out in Norway, 14,15 the risk factors for disability pension and prognostic factors for back pain included being female; low education level and low socioeconomic condition; comorbidities; fatigue; and low professional qualifi cations.…”
Section: Introductionmentioning
confidence: 99%
“…Disability and early retirement from back pain places a significant socioeconomic burden on the individual and the community and are rising exponentially [15]. Most of the costs linked to the treatment of back pain apply to a small proportion of sufferers experiencing persistent symptoms leading to disability [5,25].…”
Section: Introductionmentioning
confidence: 99%